Growth, mortality and recruitment of commercially important fishes and penaeid shrimps in indonesian waters / A. Dwiponggo, T. Hariati, S. Banon, M. L. Palomares, D. Pauly - Dwiponggo, A. (1986)
Project background, mateial and methods, results and discussion. Col. Pesc